Validation of an eBAT as a mobility aid for blind people - Abreu, David; Codina, Benito; Toledo, Jonay; Suárez, Arminda (Assistive technology, 2022)
One of the challenges faced by blind persons to achieve optimal mobility is the detection and avoidance of obstacles located in their travel path. Besides the widely used white cane, alternative or complementary devices have been developed, such as electronic aids that provide feedback about the environment. However, the devices available have been unable to provide an optimal solution with widespread acceptance, motivating the present work. The eBAT (electronic Buzzer for Autonomous Travel) is designed to offer optimal protection and employs the user's own mobile phone for easier use and reduced manufacturing costs. For this work, a group of 25 blind individuals was used to validate the eBAT based on the single-subject with reversal method (ABA study). The results show a significant decrease in the number of involuntary contacts in an unknown travel path between the first phase of the study, which did not involve the eBAT, and the second, where it was used. When the device was again removed in the third phase, the number of contacts rose. We may therefore conclude that the eBAT fills an important gap in mobility aids for blind people, yielding a clear benefit by reducing the participants' feeling of insecurity.